Dopamine signaling and myopia development: What are the key challenges. (November 2017) - Zhou, Xiangtian; Pardue, Machelle T.; Iuvone, P. Michael; Qu, Jia
Abstract: In the face of an "epidemic" increase in myopia over the last decades and myopia prevalence predicted to reach 2.5 billion people by the end of this decade, there is an urgent need to develop effective and safe therapeutic interventions to slow down this "myopia booming" and prevent myopia-related complications and vision loss. Dopamine (DA) is an important neurotransmitter in the retina and mediates diverse functions including retina development, visual signaling, and refractive development. Inspired by the convergence of epidemiological and animal studies in support of the inverse relationship between outdoor activity and risk of developing myopia and by the close biological relationship between light exposure and dopamine release/signaling, we felt it is timely and important to critically review the role of DA in myopia development. This review will revisit several key points of evidence for and against DA mediating light control of myopia: 1) the causal role of extracellular retinal DA levels, 2) the mechanism and action of dopamine D1 and D2 receptors and 3) the roles of cellular/circuit retinal pathways. We examine the experiments that show causation by altering DA, DA receptors and visual pathways using pharmacological, transgenic, or visual environment approaches. Furthermore, we critically evaluate the safety issues of a DA-based treatment strategy and some approaches to address these issues. The review identifies the key questions and challenges in translating basic knowledge on DA signaling and myopia from animal studies into effective pharmacological treatments for myopia in children. Highlights: Retinal DA, released in response to light, is a stop signal for homeostatic control of myopic eye growth. DA exerts homeostatic control of eye growth by distinct actions of DA receptors. DA signaling modulates specific retinal pathways to modify visual functions. Studies on the unwanted effects of DA agents on visual and systemic functions are needed.